An in-place truncated Fourier transform. (May 2022) - Coxon, Nicholas
Abstract: We show that simple modifications to van der Hoeven's forward and inverse truncated Fourier transforms allow the algorithms to be performed in-place, and with only a linear overhead in complexity.